Canal wall up versus canal wall down mastoidectomy - 10 years experience - Sousa, Ana Castro (2013)
Objective: To present our experience in surgical treatment of chronic otitis media with cholesteatoma (COMC), analyzing the two main surgical approaches: Canal Wall Up Mastoidectomy (CWUM) and Canal Wall Down Mastoidectomy (CWDM).Methods: Retrospective observational quantitative description. We consulted the clinical records of 150 patients with COMC undergoing CWUM or CWDM from the period between January 2002 to December 2011. We analyzed several variables such as age, sex, surgical technique, recurrence rate and functional gain (Hearing Outcomes).Results and Conclusions: CWDM procedure was performed in 76 (51%) patients and MCWU was performed on 74 (49%) patients. Ossiculoplasty surgery time was done in 101 patients simultaneously. The location of the COMC was predominantly in the attic and mastoid antrum. Recurrence rate was 10% (15 patients), mainly patients submitted to CWUM. Considering pre and post-operative air-bone gap (ABG) from both procedures, it was found that there was an average decrease of ABG in the CWUM of 4.2±11.8 and an average increase in CWDM of 0.2±12.1. Given the results of this study it is concluded that the gain function is best when using the CWUM, however, the recurrence rate was considerably higher in the respective technique.